2022
DOI: 10.32890/mjli2022.19.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Grit and Well-Being of Malaysian Esl Teachers

Abstract: Purpose – Seligman’s well-being theory of PERMA has been proven fruitful in defining various well-being constructs across different fields of study. With a growing interest in teacher psychology research abroad, PERMA has been unveiled as a rewarding prospect for the well-being of second language (L2) teachers. Nonetheless, the contribution of PERMA to the well-being and grit of L2 teachers in Malaysia remains unclear. Thus, this study (1) examined the influence of PERMA on the well-being and grit of Malaysian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(147 reference statements)
1
7
0
Order By: Relevance
“…Feeling at least some positive emotions in a day was associated with higher levels of 20 EDUCATOR EMOTIONS AND WELLBEING wellbeing than no positive emotions-almost an entire standard deviation above those with no positive emotions reported. This supports research which highlights the potential of positive emotions to mediate wellbeing and educator persistence in the face of some negative feelings (Dreer, 2024;Shanmugam & Hidayat, 2022). In this sample, educators who reported all positive emotions within a day recorded higher average levels of wellbeing over those categorized into the two other emotional groups.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Feeling at least some positive emotions in a day was associated with higher levels of 20 EDUCATOR EMOTIONS AND WELLBEING wellbeing than no positive emotions-almost an entire standard deviation above those with no positive emotions reported. This supports research which highlights the potential of positive emotions to mediate wellbeing and educator persistence in the face of some negative feelings (Dreer, 2024;Shanmugam & Hidayat, 2022). In this sample, educators who reported all positive emotions within a day recorded higher average levels of wellbeing over those categorized into the two other emotional groups.…”
Section: Discussionsupporting
confidence: 83%
“…Many of these studies have demonstrated the unique importance of positive emotions for teacher wellbeing. For example, higher levels of positive emotions have been found to significantly predict higher levels of overall wellbeing on average (Dreer, 2024;Fatih et al, 2019;Shanmugam and Hidayat, 2022;Wessels & Wood, 2019). These findings indicate that intentional boosts to teachers' experiences of positive emotions may be an important strategy for school leaders to employ to promote educator flourishing and wellbeing-and to subsequently evade issues associated with compromised wellbeing.…”
Section: Educator Emotions and Wellbeingmentioning
confidence: 98%
See 1 more Smart Citation
“…Chen and Tang (2024) support that resilience and well-being promote teachers' engagement contributing to professional success. Shanmugam and Hidayat (2022) demonstrate the importance of engagement in enhancing teachers' dedication and perseverance. Shao (2023) states enthusiastic teachers find the purpose and meaning in their work, which improves their overall well-being.…”
Section: Engagementmentioning
confidence: 90%
“…These aspects strengthen a persevering attitude toward work tasks. In addition, other studies ( Goh et al, 2022 ; Shanmugam and Hidayat, 2022 ) suggest that workers with a higher level of Grit tend to be more motivated toward the tasks assigned to them, as they feel identified and perceive progress toward the established goals. This has been mentioned within the framework of Seligman’s PERMA model, which addresses the domain of achievement and involves moving toward goals with constant effort and active work ( Donaldson et al, 2021 ; Jimenez et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%